Konstruksi Etika Digital Mahasiswa melalui Internalisasi Norma Sosial dan Budaya di Era Transformasi Teknologi - Zainal Ruma (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2026)
The era of digital transformation has significantly changed the way students interact, communicate, and construct their ethical behavior in academic and social environments. These changes require a deeper understanding of how social norms and cultural values are internalized in shaping students’ digital ethics. This study aims to analyze the construction of students’ digital ethics through the internalization of social norms and cultural values among students of the Accounting Study Program. This research employed a descriptive qualitative approach, with data collected through questionnaires distributed via Google Forms. The data were analyzed descriptively to identify students’ understanding, awareness, and implementation of ethics, social norms, and cultural values in digital interactions. The findings indicate that most students demonstrate a high level of ethical awareness in the digital environment, particularly in maintaining academic integrity, avoiding plagiarism, communicating politely, and acting responsibly in online spaces. Cultural values such as mutual cooperation, politeness, respect, and responsibility remain relevant and contribute positively to the formation of students’ ethical behavior. In addition, social environments and peer interactions play an important role in strengthening ethical awareness and shaping students’ character in the digital era. Therefore, the internalization of social norms and cultural values needs to be continuously reinforced in higher education so that students are able to develop digital ethics based on integrity, responsibility, and cultural awareness amid rapid technological transformation